2016
DOI: 10.1111/jfpp.12868
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Shelf Stability of Sugarcane Juice with Natural Preservatives

Abstract: Extracts of moringa seed and leaf (Moringa oleifera); lemon (Citrus limon) and ginger (Zingiber officinale) were added to fresh sugarcane juice in different combinations and evaluated on storage at 2, 4 and 30C. Combination of moringa seed extract with lemon and ginger showed high antimicrobial activity when compared with sodium benzoate (as chemical preservative), at the permitted level. Lemon lowered the pH of sugarcane juice to 3.01 and inhibited the growth of microorganisms during storage. Further, phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…Saxena et al reported pH values and soluble solids for raw cane juice of 4.42 and 19.6 °Brix, respectively. In a study by Ramachandran et al on the optimization of cane juice's shelf life, the pH value was 5.2. Sanda et al reported a pH of 5.28.…”
Section: Resultsmentioning
confidence: 99%
“…Saxena et al reported pH values and soluble solids for raw cane juice of 4.42 and 19.6 °Brix, respectively. In a study by Ramachandran et al on the optimization of cane juice's shelf life, the pH value was 5.2. Sanda et al reported a pH of 5.28.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of sucrose might be caused by the acid invertase enzymes that are produced by a few yeast species in the preserved juice (Hanko & Rohrer, 2000). In previous studies, several microorganisms (e.g., lactobacillus, yeast and molds) were also isolated, which were responsible for the spoilage of sugars and caused discoloration and the reduced the pH of SSJ (Bhatia, Uppal, Thind, & Batta, 2009;Ramachandran et al, 2017;Rao et al, 2012). Sucrose was converted into dextran though dextransucrase enzyme from Leuconostoc spp (Kin & Robyt, 1995).…”
Section: Sugars Concentration In the Presence Of Chemical Preservatmentioning
confidence: 99%
“…Sucrose was converted into dextran though dextransucrase enzyme from Leuconostoc spp (Kin & Robyt, 1995). In previous studies, several microorganisms (e.g., lactobacillus, yeast and molds) were also isolated, which were responsible for the spoilage of sugars and caused discoloration and the reduced the pH of SSJ (Bhatia, Uppal, Thind, & Batta, 2009;Ramachandran et al, 2017;Rao et al, 2012). The above microorganisms were also isolated from the fresh SSJ in the pre-experiments.…”
Section: Sugars Concentration In the Presence Of Chemical Preservatmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents obstacles to its industrial-scale production because it limits the manufacturer's opportunities. (Ramachandran et al, 2017). Considering the growing interest in the ready-to-drink cane juice, the development of processing technologies which promote security and stability, enable better distribution, and encourage the agroindustry is highly relevant.…”
Section: Introductionmentioning
confidence: 99%